The Analysis of CALL, Discussion and Lecture Method Toward Students’ Speaking Skills - Tekat Sukomardojo (Syntax Corporation Indonesia, 2022)
Technology and education is rapidly expanding and cannot be separated to each other. One of them is computer-assisted language learning (CALL), which is used to learn English. CALL is a computer-aided learning media used in education that is simple to access, disseminate, and save. Following that, this study attempted to determine the impact of CALL media with lecture technique and discussion on the cadets' English-speaking skills. This study employed a quantitative approach and descriptive quantitative analysis to uncover issues that arose during English learning. By reviewing the learning process, which involved 50 cadets from both classes A and B, statistical analysis was used. The results revealed a substantial difference in the use of CALL media in the lecture style and the discussion on English speaking skill.